Some music for the Kalumbu - Davidson, Marjory (International Library of African Music, 1965)
The kalumbu or musical bow is probably found more often than any other indigenous instrument in Zambia. I have been able to make a careful study of several of these instruments and there are many points of interest both in the tuning and general layout of the music. Two of my players used a large bow which they said was peculiar to the Ila people. The calabash resonator is from some kind of pumpkin which they call kankuli. The instrument can be tuned by moving the calabash, which is attached to a piece of wire acting as bridge, up or down the stick.
Keywords: Ethnomusicology; Mbira; Music; Musical instruments; Mbira music; Zambia; African Music; Mbira (Instrument)